Immunosuppression Profile of CFZ533 (Iscalimab), a Non-Depleting Anti-CD40 Antibody, and the Presence of Opportunistic Infections in a Rhesus Monkey Toxicology Study. (July 2022) - Flandre, Thierry D.; Mansfield, Keith G.; Espié, Pascal J.; Rubic-Schneider, Tina; Ulrich, Peter
CFZ533 (iscalimab) is a nondepleting anti-CD40 antibody intended for inhibition of transplant organ rejection and treatment of autoimmune diseases. In a safety assessment in rhesus monkeys, CFZ533 was administered for 13 weeks up to 150 mg/kg/week subcutaneously. CFZ533 was shown previously to completely inhibit primary and secondary T-cell-dependent antibody responses. CD40 is expressed on B cells, antigen-presenting cells, and endothelial and epithelial cells, but is not expressed on T cells. Here, we demonstrate the complete suppression of germinal center formation in lymphoid organs. CFZ533 was well tolerated and did not cause any dose-limiting toxicity. However, the histological evaluation revealed increased numbers of CD4 + and CD8 + T cells in the T-cell-rich areas of lymph nodes enlarged in response to observed adenovirus and Cryptosporidium infections which suggest that T-cell immune function was unaffected. Background infections appear as the condition leading to unraveling the differential immunosuppressive effects by CFZ533. The presence of T cells at lymph nodes draining sites of infections corroborates the immunosuppressive mechanism, which is different from calcineurin-inhibiting drugs. Furthermore, CFZ533 did not show any hematological or microscopic evidence of thromboembolic events in rhesus monkeys, which were previously shown to respond with thromboembolism to treatment with anti-CD154 antibodies.